Assessing the Use and Impact of Anti-Social Behaviour Orders. - Matthews, Professor Roger (Researching criminal justice series., 2007)
This book provides one of the first assessments of the widely used but extremely controversial Anti-Social Behaviour Orders (ASBOs) as a method for dealing with anti-social behaviour in the UK.